A modified axillo-femoral perfusion for acute type a aortic dissection accompanied with lower limb malperfusion - Li, Qianzhen (J Cardiothorac Surg, 2020)
BACKGROUND: Lower limb malperfusion accompanied with acute type A dissection (AAD) is reported to be an independent predictor for mortality. Timely treatment is required. However, staged approach to restore the perfusion of the ischemic leg before aortic repair has a continuously increase risk of aortic rupture. Aortic repair under isolated axillary artery perfusion also has the risk of prolonging leg ischemia. Here we introduce our experience in performing axillo-femoral perfusion, which is supposed to bring benefits for treating lower limb malperfuison. METHODS: Thirty patients who suffered AAD accompanied by lower limb ischemia enrolled in our study. All patients received aortic repair as soon as possible using the modified axillo-femoral perfusion approach. The cardiopulmonary bypass and cooling started with the right axillary artery perfusion. Then the femoral artery of the ischemic side was exposed and sewn to a graft connected with another inflow cannula. The rectal temperature was about 31 °C when the femoral perfusion started. The perfusion of the ischemic legs preoperative was estimated after the surgery by the clinical signs, the saturation of the distal-limb, and computed tomography scan. RESULTS: Twenty-eight patients got good perfusion of the lower body after the surgery. Two patients received femoral-femoral artery bypass immediately after surgery because of the thrombosis in the right common iliac artery, without further injury. No peripheral vessels damage occurred, and no compartment fasciotomy or amputation needed. One patient died for the sepsis and the subsequent multi organ failure 28 days postoperative. CONCLUSIONS: The modified axllio-femoral perfusion could restore the lower limbs’ perfusion simultaneously during the aortic surgery without neither delaying dissection repair nor prolonging the ischemic time. It is a simple, but safe and effective technique.